Wayang Kreasi Berbasis Sejarah Lokal Lampung untuk Penguatan Karakter Kebangsaan Siswa Sekolah Dasar - Muhammad Iqbal Rasyid; Andri Wicaksono; Yulia Siska (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2025)
Learning local history in elementary schools still faces various challenges, including students’ limited understanding of regional history and the weak internalization of national character values. One effort to address these issues is through the use of learning media based on local culture. This study aims to describe the development and feasibility of creative wayang based on Lampung local history as a learning medium for strengthening national character in elementary school students. The creative wayang was developed by incorporating the historical struggle of Radin Intan II, a local hero whose story embodies values of nationalism, courage, and love for the homeland. This study employed a research and development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. Data were collected through expert validation and questionnaires distributed to teachers and students. The results indicate that the creative wayang based on Lampung local history is considered highly feasible and engaging as a learning medium. It creates a more contextual, interactive, and meaningful learning environment for students. In addition to improving students’ understanding of local history, the use of creative wayang contributes to strengthening national character values, such as nationalism, patriotism, and respect for national heroes. Therefore, creative wayang based on local history has strong potential as an alternative cultural-based learning medium in elementary education.